Dinamika Pembinaan Agama dan Transformasi Nilai Keluarga Sakinah pada Komunitas Pengajian Ibu-Ibu At Taufiq Dusun Gayam, Mojopuro, Wonogiri - Indriani, Yundari; Natasya, Hilda; Nurzaky, Ahmad; N, Nasichah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The family is the smallest unit in society that plays an important role in shaping a generation that is faithful, morally upright, and prosperous. However, the development of the times and modern social challenges often affect the harmony and resilience of families. This community service activity aims to increase the understanding and awareness of mothers in Dusun Gayam, Mojopuro Village, Jatiroto Sub-district, Wonogiri Regency, about the concept of a blissful family through religious studies conducted in regular study forums. The implementation methods include interactive lectures and continuous guidance on Islamic values in building a harmonious, loving, and responsible household. The results of the activity show an increase in participants' understanding of the principles of a blissful family, such as good communication among family members, balanced role-sharing, and strengthened spirituality through communal worship. In addition, this activity also strengthens the bond among members of the study group and fosters the spirit to apply Islamic values in daily family life. Thus, this development program is expected to be a concrete step in forming a religious, harmonious, and prosperous society.